The Analysis Of Synchronous And Asynchronous Online Media In English Learning During Covid 19 - Armansyah; Riswanto; Zasrianita, Fera (JPT : Jurnal Pendidikan Tematik, 2020)
Online learning uses technology to help students and teachers with distance learning, with teachers who provide teaching materials that are easily accessible.This study aims to describe the implementation of learning carried out by teachers by using synchronous and asynchronous such as Google Meet, Google Classroom, and Whats App. This research was designed as a descriptive qualitative study using interview. The subjects of this study were teachers at SMA N 1 Bengkulu Tengah. Data analysis was carried out using the data proposed by Miles and Huberman to collect data. The results showed that online learners had barriers namely poor networks, the quality of mobile phones that did not support the students themselves and the capacity of the application used in online learning.